OsGRP3 Enhances Drought Resistance by Altering Phenylpropanoid Biosynthesis Pathway in Rice (Oryza sativa L.) - Xu, Wuwu; Dou, Yangfan; Geng, Han; Fu, Jinmei; Dan, Zhiwu; Liang, Ting; Cheng, Mingxing; Zhao, Weibo; Zeng, Yafei; Hu, Zhongli; Huang, Wenchao (International journal of molecular sciences, 2022)
As a sessile organism, rice often faces various kinds of abiotic stresses, such as drought stress. Drought stress seriously harms plant growth and damages crop yield every year. Therefore, it is urgent to elucidate the mechanisms of drought resistance in rice. In this study, we identified a glycine-rich RNA-binding protein, OsGRP3, in rice. Evolutionary analysis showed that it was closely related to OsGR-RBP4, which was involved in various abiotic stresses. The expression of OsGRP3 was shown to be induced by several abiotic stress treatments and phytohormone treatments. Then, the drought tolerance tests of transgenic plants confirmed that OsGRP3 enhanced drought resistance in rice. Meanwhile, the yeast two-hybrid assay, bimolecular luminescence complementation assay and bimolecular fluorescence complementation assay demonstrated that OsGRP3 bound with itself may affect the RNA chaperone function. Subsequently, the RNA-seq analysis, physiological experiments and histochemical staining showed that OsGRP3 influenced the phenylpropanoid biosynthesis pathway and further modulated lignin accumulation. Herein, our findings suggested that OsGRP3 enhanced drought resistance in rice by altering the phenylpropanoid biosynthesis pathway and further increasing lignin accumulation.